THE RELIGION FORUM AND SOCIAL CHANGE IN THE CENTER OF RADICALISM: An Effort to Counter-Radicalism and Deradicalization in The Coastal Pantura Lamongan - Bakhruddin Fannani; Moh. Anas Kholish; Nur Arifuddin; Nada Oktavia (IAIN Ponorogo, 2023)
The Islamic cleric, through religious forums managed structurally and culturally, is considered one of the essential variables in coloring the perspective of the Lamongan North Coast community amid the emergence of radicalism, which later provided intense penetration. Through the religious pulpit of NU and Muhammadiyah Islamic clerics on the North Coast of Lamongan, it promotes the importance of tolerance values of religious moderation and balance of perspectives as a counter-discourse to the narrative of radicalism that threatens the integrity of the Unitary Republic of Indonesia. While on the other hand, Muhammadiyah Islamic clerics, through religious forums, also often promote al-Ma'un theology as a teaching of compassion for the poor and Mustadh'afin in the North Coast of Lamongan. It began to emerge in various Halaqah managed by radical groups.